Analisis Tingkat Kepuasan Masyarakat Melalui Pelayanan Informasi Pada Aplikasi KRL Access - Ratnawaty Marginingsih*; Isnurrini Hidayat Susilowati; Wiwik Widiyanti (LPPM Universitas BSI, 2020)
Transportation is a very important and strategic means of smoothing the wheels of the economy. Along with the increasing needs of urban communities for transportation in general, the railroad has become one of the alternative transportation options that are increasingly in demand by people with many advantages such as low pollution, free of traffic, mass, cheaper cost, and also relatively faster time. This study aims to determine the level of community satisfaction through information services on the KRL Access application. A total of 250 respondents were sampled as research using the convenience sampling method. The form of research used is descriptive research with a quantitative approach. The data is processed using multiple linear regression analysis. The results obtained by the level of community satisfaction through information services on KRL Access applications partially and simultaneously by using the variables of reliability, responsiveness, assurance, empathy and tangible obtain positive and significant results. This shows that good service is one of the keys to an organization's success because it will have a direct impact on the company's image.